A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from the central and western Amazon and rio Paraná-Paraguai basins - Ota, Rafaela P.; Lima, Flávio C. T.; Pavanelli, Carla S. (Zootaxa, 2015)
A new species of Hemigrammus is described from the middle rio Solimões/Amazonas and tributaries, upper and middle rio Madeira, and rio Paraná-Paraguai basins in Brazil and Paraguay. The new species is most similar among congeners with Hemigrammus marginatus, with which it shares similar caudal-fin pigmentation pattern. The new species can be distinguished from Hemigrammus marginatus by possessing two conspicuous dark patches of pigmentation on caudal fin, occupying most of caudal-fin lobes, except the tips, by having two dark narrow stripes along anal-fin base, and by possessing 5–8 pored lateral line scales. The new species differs from Hyphessobrycon diancistrus, which is similar in color pattern and general body shape, by the presence of small scales on caudal-fin lobes, occupying approximately its basal third, by the presence of two narrow stripes along anal fin base, and by the absence of bony hooks on analfin in mature males. The occurrence of the new species in both Amazon and rio Paraná-Paraguai basins is discussed in order to clarify and expand recent discussions on the biogeographical relationships between both river systems.